Kontribusi ekonomi remitansi bagi pembangunan desa: Studi kasus pedagang warung tegal di Jakarta Selatan - Nur Ali Hidayatulloh; Rakhmat Hidayat (Jurnal Kependudukan Indonesia, 2022)
Warung Tegal or warteg (a food stall with cheap food) is a local economic phenomenon that is rapidly growing in the Jakarta area, particularly for the lower middle-class society. This growth is due to the connection between warteg business and remittances sent to their hometowns. This paper aims to (i) explain the informal economy of warteg traders who provide economic opportunities for other migrants in Jakarta, (ii) describe the remittances economy of warteg traders to their families in their hometowns, and (iii) explain the economic contribution of remittances to the development of migrants' origin villages. This research uses a qualitative approach with case studies of warteg traders around Bangka IX, Pela Mampang, and Mampang Prapatan. Data were obtained by direct observation that was carried out from March 2016 to January 2017. The interviewees include five warteg traders who sell in the Pela Mampang region, as well as the children of the traders and village officials of Dukuhjati Kidul, Tegal. The results of the study show that warteg can increase the wealth of migrant families. Remittances serve as a form of social bonding and responsibility to their families. They are used for consumption and productive activities, such as building houses that are considered a symbol of success in running warteg.